Evaluation ofserum levels of IL-10and IL-6 in patients with HCV at Diwaniyah Teaching Hospitals, Iraq - Syoof khoman Alramahy; Najwan abdul karim (Al-Qadisiyah Journal of Pure Science, 2019)
Hepatitis C virus (HCV) infection constitute serious global health problems due to their high morbidity and mortality.This study evaluated the serum cytokine levels (IL-10 , IL-6) of hepatitis B, as well as the differences in such levels between patients and healthy controls.30 blood samples from patients infected with HCV and 30 blood samples from healthy individuals as a control group were collected from the unit of Viruses at Diwaniyah Teaching Hospital, Women's Hospital and Educational Children in Diwaniyah Governorate, duringthe period from July 2018to February2019. In this study ELISA technique indicated that serum levels of IL-10 and IL-6 were irregular in patients with HCV , the level of  IL-10 was decreased significantly in patients with HCV (24.05±115.64) compared to control group (147.62±234.71),whereas IL-6 level was increased non significantly in patients with HCV (244.96±385.11) pg/ml compared with control group (210.45±287.15) pg/ml. Conclusionfrom the current study,low level of IL-10 in patients with HCV compared to control group, high level of IL-6 in patients with HCV compared to control group.